Assessment of Compliance with Preliminary Environmental Investigations for Erecting Sustainable Building Structure in Abuja Metropolis, Nigeria - Ibrahim, M. B.; Dauda, I.; Igwe, C. O.; Hassan, A. M. (Journal of Sustainability and Environmental Management, 2022)
The continuous collapse of structures which is usually accompanied by great loss of lives and properties, the conscientious construction activities in the country has a direct or indirect impingement on the environment by displacing settlements, hampering farming activities and the destruction of beneficial plants. This pose threats to the continuous existence of man and the sustenance of natural vegetation. Based on the foregoing, the study was designed to assess compliance with preliminary environmental investigations for erecting sustainable building structures in Abuja Metropolis. Two research questions and two null hypotheses guided the study. The research was carried out in Abuja Metropolis Nigeria. Descriptive survey research design was used for the study. The targeted population for the study was 148 subjects comprising of 72 builders and 76 engineers. Since the population was manageable no sampling was done. A structured questionnaire was used for data collection. Cronbach’s alpha statistical tool was used to determine the internal consistency of the instrument and was found to be 0.80. Data collected for the study was analyzed using mean, standard deviation and z-test. Mean was used to analyze the research questions while z-test was used to test the hypotheses at 0.05 level of significance. The findings of the study revealed that builders and engineers are aware of all the necessary preliminary investigations that should be conducted before erecting building structures. The findings also showed that despite the fact that builders and engineers are aware of the necessary preliminary environmental investigations to be conducted before erecting building structures, they still fail to execute the investigations of the building which aren’t environmentally friendly. Based on the findings of the study, it is recommended that all the preliminary investigations identified in this study should be made a requirement for approving any building plans and construction and also government should enact laws to punish violators of preliminary investigations in Nigeria.